Strategic procurement practices and organizational performance - Utibe Umoh Mbuk; Kelechi Ugwu; Dr. Obichere Jude-Kenedy Chibuzo (YAYASAN MITRA PERSADA NUSANTARA, 2026)
This study examined the relationship between strategic procurement practices and organizational performance in the Rural Access and Agricultural Marketing Project (RAAMP) in South-South Nigeria. Using a correlational survey design, data were collected from 77 SPIU staff via structured questionnaires and analyzed with descriptive statistics and linear regression. The results indicate that effective procurement planning significantly improves organizational efficiency (R² = 0.989, B = 1.024, β = 0.994, p = 0.000), highlighting the importance of prioritizing procurement planning as a strategic tool for achieving sustainable performance in public infrastructure projects. Policymakers and project managers should prioritize procurement planning as a strategic instrument for ensuring sustainable efficiency outcomes in similar infrastructural programs. Managers should prioritize SRM initiatives, as they yield measurable improvements in delivery timelines, quality, and stakeholder trust. The study provides insight for managers to adopt digital procurement tools for optimal utilization of resources to minimize waste and boost performance outcomes and project sustainability. This study enriches existing literature on procurement and performance by constructing a regression model that empirically quantifies the strength of procurement planning’s impact (R² = 0.989, β = 0.994) using context-specific data from RAAMP, thereby providing a data-driven perspective on how strategic procurement practices enhance organizational efficiency.